sir this is quadratic equations based on common root problems

Asked by Aravindh Nandha Raj s | 30th May, 2013, 07:01: PM

Expert Answer:

Let m be the common root. Then, 
a = -(m^2+12)/m
b =  -(m^2+15)/m
Also, m^2+(a+b)m+15=0
Substituting the value of a and b 
 -(m^2+12)/m + 
m^2 -2m^2-27+15 = 0
m^2 = -13
m = sqrt(13)i
a = -(m^2+12)/m = 1/sqrt(13)i = -sqrt(13)i/13
b =  -(m^2+15)/m = -2/sqrt(13)i = -2sqrt(13)i/13

Answered by  | 31st May, 2013, 04:55: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.